ISSUES OF EDUCATIONAL AND SPIRITUAL FORMATION OF THE YOUNGER GENERATION IN THE WORK OF MUKHAMMAD AZ-ZAMAKHSHARI “ATVOK-UZ-ZAHAB” - J. Mirakhmedov (Galaxy International Interdisciplinary Research Journal, 2023)
This article explores the issues of Education and spiritual formation of the younger generation in the work of Mukhammad az-Zamakhshari “Atvok-uz-zahab”. In addition, the work of Mukhammad az-Zamakhshari “Atvok-uz-zahab” highlights the need to educate the younger generation from youth, for which the example of upbringing, parents, murabians is important, their upbringing of their own children is scientific, intelligent.